2016
DOI: 10.1292/jvms.16-0202
|View full text |Cite
|
Sign up to set email alerts
|

Rapid absorption of diclofenac and acetaminophen after their oral administration to cattle

Abstract: The oral pharmacokinetics of diclofenac (DF) were evaluated in cattle by analyzing plasma concentration-time data after its intravenous and oral administration in order to propose the oral administration of DF as effective route to avoid long withdraw period. DF was intravenously and orally administered at 1 mg/kg to cattle using a crossover design with a 4-week washout period. Plasma concentrations of DF were determined by a HPLC analysis. The mean absorption time (MAT) and absorption half-life (t1/2ka) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
2
0
4
Order By: Relevance
“…Diclofenac was detected in all SWI soils (maximum: 15.90 μg kg −1 minimum: 2.80 μg kg −1 ). The presence of this compound is consistent with its wide use as an anti-inflammatory drug and a painkiller in pigs (Cevc & Blume, 2001) and cattle (Sawaguchi et al, 2016).…”
Section: Analysis Of Pharmaceuticalssupporting
confidence: 66%
“…Diclofenac was detected in all SWI soils (maximum: 15.90 μg kg −1 minimum: 2.80 μg kg −1 ). The presence of this compound is consistent with its wide use as an anti-inflammatory drug and a painkiller in pigs (Cevc & Blume, 2001) and cattle (Sawaguchi et al, 2016).…”
Section: Analysis Of Pharmaceuticalssupporting
confidence: 66%
“…Verder is gebruikt gemaakt van de veterinaire database FARAD waar een overzicht is beschreven van alle literatuur wat betreft paracetamol in runderen (https://cafarad.ucdavis.edu/citationsearch/). Er zijn twee studies gevonden die de orale opname van paracetamol in runderen/kalveren beschrijven en deze zijn opgenomen in Tabel 3.2 (Janus et al, 2003;Sawaguchi et al, 2016).…”
Section: Beschikbare In Vivo Dataunclassified
“…De halfwaardetijd in het maag/darmkanaal was 1,6 uur. In het model wordt de opnamesnelheid van paracetamol gebruikt als PBK inputparameter, namelijk 0,472 per uur (Sawaguchi et al, 2016). Verder wordt aangenomen dat paracetamol voor 100% wordt opgenomen en dat de pens niet bijdraagt aan metabolisme.…”
Section: Opname (Toedieningsroute)unclassified
See 1 more Smart Citation
“…These data demonstrate that both the absorption and elimination of injected p-acetaminophen are faster in porcine animals than in Bactrian camels. Sawaguchi et al [8] studied the pharmacokinetics of p-acetaminophen in healthy cattle following oral administration and reported that T max was 1.40 ± 0.55 h, T 1/2 was 2.41 ± 0.58 h, and the MRT was 4.70 ± 0.93 h. Yamasaki et al [9] reported that T 1/2 was 0.30 ± 0.02 h and the MRT was 0.40 ± 0.03 h in rats upon intramuscular injection of p-acetaminophen, revealing that it is eliminated quickly by rats. Comparing these previously reported data with those obtained in the current study (Table 1) reveals that T max , T 1/2 , and MRT for p-acetaminophen in Bactrian camels is higher than that in pigs, cows, and rats.…”
mentioning
confidence: 99%